SURVEY: ENHANCING ENERGY PROFICIENCY IN SMART MOBILE DEVICES USING COMPOSITE OFFLOAD DECISION ALGORITHMS - S K, Sridhar; J, Dr. Amutharaj; Vijayanand, Dr. S (The journal of contemporary issues in business and government, 2021)
The resource limited mobile devices are the foremost confronter for the growth of Mobile Computing. Although the advance development of mobile applications are able to provide substantial benefits to end users as and when required through continuous online services and accessibility, it has become quite formidable to relish the mobile computing services to its maximum capability due to energy paucity and non availability of effective and collaborative decision making component. So the combination of local, remote mobile cloud computing and a quick collective offload decision that makes a flawless task offloading can intensify to novel computing as an added feature to mobile cloud computing (MCC) to enhance mobile device performance and utilize the available energy proficiently. The proposed framework consists of three major components namely, mobile client, local mobile device cloud (LMC) and remote cloud. These components communicate with each other to generate a composite offload decision based on several system parameters that accounts to enhanced energy proficiency and performance.